Based on the information given in the exercise, you can set up the following System of equations:
![\begin{cases}3p-2q=4 \\ 7p-3q=1\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/kgkr02ckzk2rmee6pyoq59d8pzi2u3sib1.png)
You can use the Substitution method to find the value of the variable "p" and the variable "q":
- Solve for "q" from the first equation:
![\begin{gathered} 3p-2q=4 \\ -2q=4-3p \\ q=(4)/(-2)-((3p)/(-2)) \\ \\ q=-2+(3)/(2)p \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n08xd8zbtvrl3p96lp6c5g8rpl9gsx5ks8.png)
- Substitute the new equation into the second equation:
![\begin{gathered} 7p-3q=1 \\ 7p-3(-2+(3)/(2)p)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uvyojb0pmymbchvq5d1mmd14jqptgp1ycr.png)
- Solve for "p":
![\begin{gathered} 7p+6-(9)/(2)p=1 \\ \\ (5)/(2)p=1-6 \\ \\ 5p=(2)(-5) \\ \\ p=(-10)/(5) \\ \\ p=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/er9x3rk3n94w407dbdz0euxfu3k8zkbedg.png)
- Substitute the value of "p" into the equation
![q=-2+(3)/(2)p](https://img.qammunity.org/2023/formulas/mathematics/college/z6zj6umhhima3bolmg24qegalz7f3e413k.png)
And evaluate. Then:
![\begin{gathered} q=-2+(3)/(2)(-2) \\ q=-2-3 \\ q=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4mxl4u0ifb22bf8pc6bwrxf3plfb713hoj.png)
Now knowing the values of "p" and "q", you can substitute them into this expression:
![4p-5q](https://img.qammunity.org/2023/formulas/mathematics/college/l2gt20aa1btaqbwd7lx6voejsmq8vt3vwa.png)
And then evaluate. So, you get:
![4(-2)-5(-5)=-8+25=17](https://img.qammunity.org/2023/formulas/mathematics/college/3r9blqfr8wi0h1sj2vi5rb6naqp4z9ntdr.png)
Therefore:
![4p-5q=17](https://img.qammunity.org/2023/formulas/mathematics/college/2bhqax37884hs68urv2f3luv6j08rijlo1.png)
The answer is: Option D.